The State of Academic Bullying Among Medical Students in Tanzania: Prevalence, Forms and Associated Factors. A Cross-Sectional Study - Harold L. Mashauri; Cornel M. Angolile; Baraka L. Max; Angela O. Makule; Ashrak M. Peter; Lisbeth Mhando; Francis Sakita (Journal of Medical Education and Curricular Development)
Introduction Academic bullying is prevalent in medical schools due to their unique study settings. Globally, the prevalence of academic bullying is increasing markedly; it ranges from 27% to 99.1%. However, the extent, forms, and associated factors of academic bullying among medical students in Tanzania are unknown. Objective To determine the prevalence, forms, and factors associated with academic bullying among medical students in Tanzania. Methodology This was a cross-sectional study among medical students in 10 medical schools in Tanzania using an online structured questionnaire. Statistical analysis included the use of frequencies, percentages, chi-square and univariate logistic regression at 95% confidence intervals (CIs) and significance at p-value <0.05. Results The study included 427 medical students. Majority (71.7%) of the medical students were in their clinical years. Among the participants, 80.8% had heard of academic bullying in medical school. Prevalence of academic bullying was 34.7% while 28.7% had a secondary experience. It was more common in clinical rotation settings (65.4%). Verbal abuse was the most common form of bullying. Factors associated with academic bullying included age, sex, marital status, religion, class category, year of study, presence of mentorship programs, having a mentor or not, presence of bullying reporting system, friendliness of bullying reporting system and students perceived overall rating of the learning environment. Conclusion Despite being relatively low compared to most countries, the prevalence of academic bullying among medical students in Tanzania is potentially of both medical education, career prosperity and mental health concern especially among medical students. Collaborative efforts among national respective authorities, medical schools and students are crucial in prevention and control of academic bullying practice.